Effect of Board and Audit Committee Attributes on Earnings Management: Evidence from Listed Non-Financial Firms in Nigeria: Audit Committee, Board Expertise, Boards’ Size, Earnings Management and Financial Expertise. - Obeitoh, Ozigi Omoyi; Yunusa, Abdulateef; Yusuf, Mohammed Aliyu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This study examines the effect of board and audit committee attributes on earnings management. The study adopts purposive sampling technique. The study carries out robust regression statistical model with a 10-year panel data among 36 listed firms in Nigeria. The data used were sourced from the published annual account and reports of sampled firms listed on the Nigeria Exchange Group. The findings from the study reveal that board size, board independence and financial expertise of women on the board and audit committee diminish earnings management while board expertise show mixed finding as board expertise promotes non-discretionary accrual, its equally diminishes discretionary accruals. The findings of this study imply that board and audit committee attributes are important in dealing with earnings management. From our key findings, the study recommends the inclusion of women with financial expertise on the board and audit committee beyond gender diversity. In contrasts to the present practice, the study recommends the inclusion of more independent directors to the board as against the current practice of non-executive directors as independent directors reduce earnings management.